Leadership and Organizational Climate on Teacher Motivation - Teuku Yasser (AL-ISHLAH: Jurnal Pendidikan, 2021)
This study aims to determine the relationship between leadership and organizational climate on teachers’ work motivation at vocational high school in Banda Aceh. This research uses quantitative research methods, and the data collection technique used is a questionnaire. Fifty teachers participated in this research. The analytical method used is the Pearson product-moment correlation. Based on the calculation, the relationship between leadership and teachers’ work motivation at vocational high school in Banda Aceh using the Pearson product-moment, the value of correlation coefficient = 0.539 is obtained with a significance level of p = 0.000 0.05. It means that there is a positive relationship between leadership and teachers’ work motivation. However, the relationship between organizational climate and work motivation teachers using the Pearson product-moment was -0.466. It is obtained with a significance level of p = 0.001 0.05. It implies a positive relationship between organizational climate and teachers’ work motivation.